2005
DOI: 10.1002/pca.820
|View full text |Cite
|
Sign up to set email alerts
|

Distinction of theC-glycosylflavone isomer pairs orientin/isoorientin and vitexin/isovitexin using HPLC-MS exact mass measurement and in-source CID

Abstract: HPLC-MS using collision induced dissociation (CID) has been utilised for the identification of the C-glycosylflavone isomer pairs orientin/isoorientin and vitexin/isovitexin. HPLC-CID/MS analyses produced pseudo-MS/MS spectra that allowed the identification of the flavone C-glycosides. The efficient differentiation of isomers was performed by comparing the CID-MS/MS spectra (including exact mass measurements) of particular fragments from the C-glycoside unit. In order to illustrate some possibilities of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 10 publications
5
76
0
5
Order By: Relevance
“…The presence of these two isomers in contiguous fractions were confirmed by HPLC-MS analysis (results not shown). Moreover, considering that in nature the C-glycosyl moieties appear almost exclusively at 6 and/or 8-positions of flavones (Cuyckens & Claeys, 2004) and that the 8-C-glycosyl-luteolin isomer elutes before the 6-C-glycosyl-luteolin under reversed phase conditions (Kazuno, Yanagida, Shindo, & Murayama, 2005;Pereira, Yariwake, & McCullagh, 2005;Piccinelli et al, 2008), the phenolic compounds in fractions 1 and 2 were respectively assigned to 2 00 -O-pentosyl-6-C-hexosyl-luteolin and 2 00 -O-pentosyl-8-C-hexosylluteolin. The structures of these two compounds are depicted in Fig.…”
Section: Luteolin Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of these two isomers in contiguous fractions were confirmed by HPLC-MS analysis (results not shown). Moreover, considering that in nature the C-glycosyl moieties appear almost exclusively at 6 and/or 8-positions of flavones (Cuyckens & Claeys, 2004) and that the 8-C-glycosyl-luteolin isomer elutes before the 6-C-glycosyl-luteolin under reversed phase conditions (Kazuno, Yanagida, Shindo, & Murayama, 2005;Pereira, Yariwake, & McCullagh, 2005;Piccinelli et al, 2008), the phenolic compounds in fractions 1 and 2 were respectively assigned to 2 00 -O-pentosyl-6-C-hexosyl-luteolin and 2 00 -O-pentosyl-8-C-hexosylluteolin. The structures of these two compounds are depicted in Fig.…”
Section: Luteolin Derivativesmentioning
confidence: 99%
“…3). Attending that 8-C-glucosyl-apigenin elutes before 6-C-glucosyl-apigenin under HPLC reverse phase conditions (Kazuno et al, 2005;Pereira et al, 2005;Piccinelli et al, 2008), compounds of MW 564 Da in fractions 4 and 5 were respectively assigned to 2 00 -O-pentosyl-vitexin and 2 00 -O-pentosyl-isovitexin. To our knowledge, these compounds were here detected for the first time in Fabaceae family.…”
Section: Apigenin Derivativesmentioning
confidence: 99%
“…We have recently demonstrated that the combination of mass measurement and in-source collision-induced dissociation (CID) is a valuable tool for the unequivocal identification of isomeric C-glycosylflavonoids in Passiflora extracts. 7 Sugarcane (Saccharum officinarum L.; Gramineae) is the main source of industrial sugar in tropical countries and is also one of the most important crop plants in Brazil. Various HPLC-UV-MS techniques (including APCI-MS/ MS and UV detection using post-column addition of shift reagents) have been employed previously in the investigation of sugarcane components, resulting in the identification of 15 flavone glycosides and aglycones.…”
Section: Introductionmentioning
confidence: 99%
“…In mono-C-hexosyl flavones, the presence of ions - -90] -was typical of the 6-C isomer (Ferreres et al, 2008(Ferreres et al, , 2007(Ferreres et al, , 2003 (Pereira et al, 2005;Ferreres et al, 2003;Sánches-Rabaneda et al, 2003).…”
Section: Mono-c-glycosyl Flavonesmentioning
confidence: 99%